Preparation of Spinel and Garnet Ferrites and Identification of Their Magnetic-Energy Losses - Yahya, Noorhana (2001)
The objective of this work was to explain the magnetic-energy loss mechanisms of some magnetic materials. The study was divided into three parts., The first part involved fabrication of NiZn-based and YIG ferrites in toroidal and pellet form, employing ceramic processing technique of the starting oxides. Characterisation of chemical, microstructural, magnetic, electrical, mechanical and thermal properties were carried out. In the second part, sol-gel method was employed to obtain high quality and fine-grained microstucture. The Y3FeS012 and NiFe204 samples were fabricated using this technique. The third part dealt with some preliminary studies on the magneto-optical Kerr effect, which were carried out on the NiFe204 and YSFeS012 samples. The characterisation of samples in the first part was divided mainly into two parts: the extrinsic-microstructure properties and the intrinsic-composition properties. The results showed that the initial permeability, relative loss factor, impedance, power loss, quality factor, saturation induction, core loss, coercive force, curie temperature and temperature coefficient of the sintered samples depended chiefly on both the microstructure and the composition of the samples. Adopting ZnO, which acted as a modifier, in the NiZn ferrite series (first premise) had greatly influenced the magnetic properties of the samples, as occurrence of Zn loss was a major factor that affected the grain growth kinetics. Adopting an iron-deficit composition (second series) was fruitful when high density and wide operating frequencies were required in the NiZn ferrite composition. Samples with excess Fe203 (third series) were deleterious in terms of losses due to the formation of Fe2+. There was no significant contribution of the zero magnetostriction affecting the magnetic and electrical properties that was concluded from this premise. CoO was seen to affect the growth anisotropy in the rich NiO content (fourth premise) and thus affected the microstructure of the samples. Interesting, however, was sample with composition Nio.8Zno.2Fe204 that gave very homogeneous and moderate grain size (:::::10.9 flm) exhibited large -KJ , played a dominant role in the frequency extension. Evidence by the reduced permeability, it was believed that the damping of domain wall was restricted by the anisotropy effects. Simultaneously, the relative loss factor was significantly reduced at higher frequencies. In the fifth premise where both C0 2 + and Fe 2 + were adopted in the excess non NiZn based composition, the C02+ content was believed to stabilise the domain wall movement at high frequencies. When a small concentration of cobalt with the formula Nio.70COO.0191sZno.27S8SFe2.00S04.00S was adopted, a vast decrease of power loss was seen to occur. It was speculated that C02+ ions diffused or moved through the vacancies and hence caused them to reside in the vacancies created by the slight iron excess. This reduced the stress and strain created by them and as a result, power loss was reduced significantly. In the second part of this work, high quality and fine grained single-phase ferrite (-0.9 Ilm) was obtained by using the sol-gel technique. Finally, Kerr rotation (Nl deg) was observed for both the NiFe204 and Y3Fes012 samples. Kerr rotation was accompanied by optical energy reflection . This was actually a measure of energy reflected when ferromagnetic order exists. This shed new light in the area of magnetooptics